Erratum to: Prognostics of Induction Motor Shaft Based on Feature Importance and Least Square Support Vector Machine Regression - Susilo, Didik Djoko; Widodo, A.; Prahasto, T.; Nizam, M. (International Journal of Automotive and Mechanical Engineering, 2021)
This is an erratum to International Journal of Automotive and Mechanical Engineering 2021; 18(1): 8464–8477. Please refer to the related article: https://doi.org/10.15282/ijame.18.1.2021.06.0641